Functional Systemic Linguistic Approach in Translation Studies of Taxis Markers in "WoY" - Retnomurti, Ayu Bandu; zuriyati, zuriyati; Anwar, Miftahulkhairah (Pujangga : Jurnal Bahasa dan Sastra, 2023)
Waiting on You (WoY) is the work of Kristan Higgins, a New York Times bestselling author whose novel was also translated into Indonesian by Nina Andiana. Higgins consistently uses complex clauses in writing novels. As a result, long complex clauses are difficult to translate. This research refers to the Functional Systemic Linguistics approach which aims to: explain the interdependence and semantic logic of complex clauses in source language text are translated into interdependence and semantic logic of complex clauses in recipient language text in novel WoY; Taxis marker translation technique used in translating from source language text to recipient language; the shifts found in the translated novel Penantian Terpanjang; the quality of translation of complex clauses in target language. This method is descriptive qualitative with taxis as an object in the novel WoY, sourced from source language texts and recipient language texts from the novel entitled Penantian Terpanjang, and obtained from informants who are linguistic and translation experts. The technique is purposive sampling. Techniques of collecting data are document analysis and focus group discussions. The data validity is triangulation. The results are after breaking down sentences into clauses and analyzing them, researchers find that the most dominant form (interdependence) is paratactic, and the meaning (semantic logic) that is most widely used is the extension. Meanwhile, the most widely used technique is common. The types of shifts found are form (interdependence) and meaning (semantic logic). This shift has a positive effect on readability so that it can improve the quality of the novel translation.